The Evaluation of Shell-and-Tube Heat Exchanger using Computer Simulation for Oil and Gas Industry - Zainulabidin, Muhd. Hafeez; ALEXIA LUKE LAITI (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Heat exchangers brings the definition of a component used to transmit heat between two or more mediums. This study will be on the evaluation of shell-and-tube heat exchanger using Computer Simulation for Oil and Gas Industry where it is to model the shell-and-tube heat exchanger by using FEA-CFD software and the effect of Malaysia’s surrounding temperature using CFD Software. It is scoped to the surrounding ambient temperature according to Malaysia’s surrounding temperature at the industry, with consideration of the mesh element sizing only limits 512,000 cells/nodes. The procedure in this study will be using Fluid Flow (Fluent) using ANSYS Simulation as it is able to create more uniform mesh for improved accuracy where it can use for internal and external characterization of fluid behavior and heat flow. The shell-and-tube heat exchanger is 1m long with an inner diameter of 100mm and outer diameter of 150mm, with copper as the material which viewed as deemed fit. The study’s result uses 100 iterations, active energy equation with mesh element sizing of 0.04m. The working pressure was assumed in environmental condition, 101.325kPa with hot inlet velocity of 10m/s and cold inlet at 0m/s. Besides that, it shows that there is near similar reading of temperature between previous studies which signifies that the hot and cold outlets proof to be compatible as the evaluation using Computer Simulation goes. In those past literature study, they mathematically model the heat exchanger using system identification methods, with the usage of Auto Regressive-Moving-Average model with eXogenous inputs (ARMAX) model obtained from Pseudo Random Binary Signal (PRBS). The other study used Computational Fluid Dynamics (CFD) with geometrical design in INVENTER PROFESSIONAL. It showed that the cooling agent (H2O) flowing inside work effectively to regulate the intense temperature inside the shell-and-tube heat exchanger. The impact of temperature and surface region is highly dependent on the heat transfer rate. However, different approach could be considered such as using more finer mesh element sizing for more accurate result. Besides that, variation of diameters on heat transfer area and other approach can be used to apply in this study.